Russian strategic directions in the Middle East goals- determinants- future dimension)) - Muhammad, Assist.Lecture .Abdullah (The International and Political Journal, 2023)
According to the contemporary Russian strategic approach, the Middle East region witnessed a gradual return to the influential role of this country, as Russia achieved great rapprochement with the region and was able to restore its relations with some of its countries. It also tended to play political and military roles in pivotal issues. This return was accompanied by an increasing desire to penetrate several regions’ countries. Such a penetration would help Russia in ensuring a better position in international interactions and open a new vital field to maximize its strategic interests.